A Simplified mAb-Based Antigen Detection Assay for Rapid Serotyping of Foot-and-Mouth Disease Virus - Mohammad A. Kashem; Thanuja Ambagala; Kate Hole; Ming Yang; Charles Nfon; Shawn Babiuk (Viruses)
Foot-and-mouth disease (FMD) is a devastating infectious viral disease of cloven-hoofed animals. Differentiating FMD from other vesicular diseases is difficult based on only clinical symptoms, requiring an appropriate laboratory diagnostic test. The double-antibody sandwich (DAS)-ELISA is a reliable diagnostic technique for antigen detection and serotyping of FMDV. However, classical DAS-ELISAs use polyclonal antibodies (pAbs), which are inconsistent in yields and limited in large-scale applications compared to hybridoma cell-secreted laboratory-made monoclonal antibodies (mAbs). Therefore, this study aimed to develop simplified and sensitive FMD serotype-specific DAS-ELISAs using HRP-conjugated mAbs and a TMB substrate. Six FMDV serotype-specific mAb-DAS-ELISAs were developed. All assays were optimized using BEI-inactivated FMD antigens. Real-time reverse-transcriptase PCR (RRT-PCR) was also used to verify the detection efficiency of all assays. Known negative and positive 10% tissue suspensions of different animal origins were examined to calculate the diagnostic specificity (DSp) and sensitivity (DSe). Serotype-specific mAb-DAS-ELISAs demonstrated 100%, 97%, 97%, 99%, 99%, and 94% DSp and 100%, 95%, 90%, 95%, 100%, and 100% DSe for serotypes O, A, Asia-1, SAT-1, SAT-2, and SAT-3, respectively. The detection efficiency of mAb-DAS-ELISAs was better than that of classical DAS-ELISAs. Also, all assays demonstrated minimal cross-reactivity and optimal reproducibility. Therefore, the mAb-DAS-ELISAs developed in this study could be useful for detecting and serotyping FMDV and ultimately replacing the classical DAS-ELISA.